2012
DOI: 10.1007/s00464-012-2262-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision versus conventional laparoscopic colectomy for colonic neoplasm: a randomized, controlled trial

Abstract: In a selected group of patients with small tumor and good operative risk, SILC is a safe alternative to CLC. Single-port laparoscopic colectomy also is associated with the benefits of less postoperative pain and shorter hospital stay than CLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(159 citation statements)
references
References 17 publications
7
145
5
2
Order By: Relevance
“…A number of reports have demonstrated its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain and shorter recovery time (31)(32)(33)(34)(35). In the current study, no statistically significant differences in short-term outcomes were found between elderly colon cancer patients who underwent MLS and SLS.…”
Section: Discussioncontrasting
confidence: 47%
“…A number of reports have demonstrated its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain and shorter recovery time (31)(32)(33)(34)(35). In the current study, no statistically significant differences in short-term outcomes were found between elderly colon cancer patients who underwent MLS and SLS.…”
Section: Discussioncontrasting
confidence: 47%
“…Single incision gastrectomy for gastric cancer or matched retrospective study, even though the number of sample size was limited (11)(12)(13)(14).…”
Section: Review Articlementioning
confidence: 99%
“…Some reports have successfully mentioned its advantages in reducing the number of laparoscopic ports, including better cosmetic results, reduced postoperative pain, and shorter recovery time. [13][14][15][16][17] To our knowledge, this is the first reported case of SILSþ1 TPE for advanced rectal cancer.…”
Section: Discussionmentioning
confidence: 73%